Da vela a vila: uma memória viva das microterritorialidades do samba na cidade de São Paulo como práticas de resistência 2000-2018 - Ferreira, Beatriz Guarnieri (2021)
This work aimed to analyze the cultural and social networks of two samba circles on the outskirts of the city of São Paulo, from 2000 to 2018: Samba da Vela Community (Santo Amaro) and Samba Community of Vila Industrial. It also aimed to problematize the motivations of the foundation of each group, to identify the people involved in this process, to verify the development of the circles as ways of maintaining a living memory of samba that is not only anchored in the present moment, but also extends in the past and occurs at different times) and to verify the ways of construction of their microterritorialities and their common bonds. For this purposo, fieldwork was carried out through interviews, questionnaires and photographic records of the most relevant places, in addition to the search for lyrics and documentaries. With a theoretical-methodological basis from the perspective of Cultural History, the Oral History method was used; therefore, memory and resistance are presented as preservation of the collectives' past and their identities that mark the places. In this sense, it is important to understand the memory of the present time as the permanence of the experiences transmitted through orality, actions, dances and music